Leishmania major-derived lipophosphoglycan influences the host’s early immune response by inducing platelet activation and DKK1 production via TLR1/2 - Ihedioha, Olivia C.; Sivakoses, Anutr; Beverley, Stephen M.; McMahon-Pratt, Diane; Bothwell, Alfred L. M. (Frontiers in Immunology, 2023)
Platelets are rapidly deployed to infection sites and respond to pathogenic molecules via pattern recognition receptors (TLR, NLRP). Dickkopf1 (DKK1) is a quintessential Wnt antagonist produced by a variety of cell types including platelets, endothelial cells, and is known to modulate pro-inflammatory responses in infectious diseases and cancer. Moreover, DKK1 is critical for forming leukocyte-platelet aggregates and induction of type 2 cell-mediated immune responses.Our previous publication showed activated platelets release DKK1 following Leishmania major recognition, and here we probed the role of the key surface virulence glycoconjugate lipophosphoglycan (LPG), on DKK1 production using null mutants deficient in LPG synthesis (Δlpg1and Δlpg2 -). Leishmania-induced DKK1 production was reduced to control levels in the absence of LPG in both mutants and was restored upon re-expression of the cognate LPG1 or LPG2 genes. Furthermore, the formation of leukocyte-platelet aggregates was dependent on LPG.LPG mediated platelet activation and DKK1 production occurs through TLR1/2. Thus, LPG is a key virulence factor that induces DKK1 production from activated platelets, and the circulating DKK1 promotes Th2 cell polarization. This suggests that LPG-activated platelets can drive innate and adaptive immune responses to Leishmania infection.